Offering branded remanufactured/recycled products: At what price? - Leila Hamzaoui-Essoussi; Jonathan D. Linton (Journal of Remanufacturing, 2014)
This paper investigates the impact of product category, perceived risk, and brand name on consumers' willingness to pay (WTP) for greener (recycled/remanufactured) products. Results provide an understanding on how consumers differentiate between types of products when stating their WTP. The findings suggest that WTP for greener versus branded greener or new products varies with product category. For paper, toner cartridges, and cell phones, brand effects are apparent. However, for cameras and printers brand does not appear to counterbalance perceived risk. As the importance of brand is a function of product category and is significantly related to WTP, original equipment manufacturers (OEMs) should carefully consider this relationship for their products before making decisions on the use of brand as a part of remanufacturing/recycling strategy.
Keywords: 650; Brand name; Willingness to pay; Remanufacturing